(6y-4)y+3=0

Simple and best practice solution for (6y-4)y+3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6y-4)y+3=0 equation:


Simplifying
(6y + -4) * y + 3 = 0

Reorder the terms:
(-4 + 6y) * y + 3 = 0

Reorder the terms for easier multiplication:
y(-4 + 6y) + 3 = 0
(-4 * y + 6y * y) + 3 = 0
(-4y + 6y2) + 3 = 0

Reorder the terms:
3 + -4y + 6y2 = 0

Solving
3 + -4y + 6y2 = 0

Solving for variable 'y'.

Begin completing the square.  Divide all terms by
6 the coefficient of the squared term: 

Divide each side by '6'.
0.5 + -0.6666666667y + y2 = 0

Move the constant term to the right:

Add '-0.5' to each side of the equation.
0.5 + -0.6666666667y + -0.5 + y2 = 0 + -0.5

Reorder the terms:
0.5 + -0.5 + -0.6666666667y + y2 = 0 + -0.5

Combine like terms: 0.5 + -0.5 = 0.0
0.0 + -0.6666666667y + y2 = 0 + -0.5
-0.6666666667y + y2 = 0 + -0.5

Combine like terms: 0 + -0.5 = -0.5
-0.6666666667y + y2 = -0.5

The y term is -0.6666666667y.  Take half its coefficient (-0.3333333334).
Square it (0.1111111112) and add it to both sides.

Add '0.1111111112' to each side of the equation.
-0.6666666667y + 0.1111111112 + y2 = -0.5 + 0.1111111112

Reorder the terms:
0.1111111112 + -0.6666666667y + y2 = -0.5 + 0.1111111112

Combine like terms: -0.5 + 0.1111111112 = -0.3888888888
0.1111111112 + -0.6666666667y + y2 = -0.3888888888

Factor a perfect square on the left side:
(y + -0.3333333334)(y + -0.3333333334) = -0.3888888888

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 2(y+8)=3(y-4) | | 64+225=x | | 1/2-x/4=17/8 | | 933x=100 | | 7024x=100 | | 2+8x=-40+x | | 4y^2=-28y | | X=x-1*x-9 | | 100x+60y=6000 | | x-x+14=0 | | 6x=2+40 | | 200x-20=100x+60 | | 200n^2+299n-2569000=0 | | 59x+22.5=105-25x | | 14-15g=4 | | -5x-64=-50x+344 | | 2/3m-1/5=5/7 | | 120x+42=100-24x | | (2x+6)(2x+8)=120 | | 37k-32=32 | | (5x^2+8x+5)-(2x^2-3x+2)= | | P(x)=5x^2-4x+8 | | 9a-2b+2=0 | | 308=-16t^2+96t+228 | | 4x-3/3=2x-1/2 | | y=3*(cosx) | | 308=-16t^2+96+228 | | (2k-1)x^2-8x+8=0 | | 2(3x+8)=2x | | 4x^2-27x+33=-3+6 | | 2(34-22-6)= | | 2(4n+8)=8 |

Equations solver categories